MINI REVIEW : PENGARUH KONSENTRASI BIOETANOL PADA PROSES FERMENTASI MENGGUNAKAN KROMATOGRAFI GAS - Kurniawan, Andi; Aswad, Muhammad Raihan; Azka, Andi Aulia Urrahman; Rizkullah, Muhammad Adhitya; Jofri, Dirga Hosea Seventin; Kartika, Rudi (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Fermentation has been used by traditional societies as far back as 6000 AD involving microorganisms such as yeast and bacteria that can convert carbohydrates into alcohol and carbon dioxide. This process is essential for the production of bioethanol produced from agricultural residues. Fermentation testing can be done using raw materials such as tubers, sticky rice, sago, water hyacinth and cassava to produce bioethanol as an alternative renewable energy. Methods This research utilizes 8 articles from national and international literature studies in the last 10 years that focus on the fermentation process to produce bioethanol. Research and development of efficient fermentation techniques is urgently needed to increase the yield and sustainability of bioethanol production, thus becoming an environmentally friendly solution in meeting global energy needs. Keywords : Bioethanol, Fermentation, microorganisms